Interaction of family history of hypertension and overweight/obesity on hypertension in Han and Manchu adults in Hebei province - JIANG Chenchen, CUI Ze, PAN Li, SUN Jixin, HE Huijing, HU Yaoda, SHAN Guangliang (Jichu yixue yu linchuang, 2023)
Objective To investigate the effects of family history of hypertension, overweight/obesity and the interaction between the two factors on hypertension in Han and Manchu adults in Hebei Province, so to provide a reference for the prevention and control of hypertension in Hebei province. Methods A cross-section survey by questionnaires investigation and physical examination was conducted in Hebei province in July to August 2017, a multistage stratified cluster sampling covering 4 633 Han and Manchu people aged 20-80 years old in Hebei province was performed. A multivariate Logistic regression model was used to analyze the effects of family history of hypertension and overweight/obesity on hypertension. Results After adjusting for ethnicity, sex, age, geographic distribution(urban/rural), economic income,education, smoking, drinking, physical exercise and daily activity, the risk of hypertension was 3.6(95% CI: 2.51-5.18) times higher in those with a family history of hypertension than those without the family history. The risk of hypertension in overweight/obese people was 2.90(95% CI: 1.92-4.37) times higher than non-overweight/obese people. The risk of hypertension was 9.78(95% CI: 6.86-13.95) times higher in population with the factors of overweight plus family history as compared to those with neither factors.The relative excess risk due to interaction (RERI) was 4.28(95% CI: 2.59-5.96), the synergy index (SI) was 1.95(95% CI: 1.54-2.47) and the attributable proportion due to interaction (AP) was 0.44(95% CI: 0.33-0.54). Conclusions Both family history of hypertension and overweight/obesity are associated with an increased risk of hypertension, and there is a positive additive interaction between the two factors.